Increasing Speaking Achievement by Using Pow-Tega Teachnique - Sri Wahyuni (International Journal of Language Teaching and Education, 2017)
The aim of this study was to find out whether or not Pow-Tega Technique could increase the students’ speaking achievement. The population of the study covered all of the tenth graders of SMA Negeri 1 Pagaralam in academic year 2015/2016. The sample was selected purposively from the population, they were sixty students. Quasi – Experimental design was used in this study. To find whether the Pow-Tega Technique could improve students’ speaking achievement, the instruction tests were used to collect the data. The data were analyzed by using paired sample t-test and independent sample t-test. The result of paired sample t-test showed that t-obtained was 3.971, t-value 2.045 (p < 0.05). Moreover, based on the result of independent sample t-test, t-obtained was 3.082, t-value was 2.002 (p < 0.05). The result showed that the students who were taught by using Pow-Tega Technique had a better improvement in their speaking achievement. In other words, Pow-Tega technique is a good way to be used by the teachers as a teaching technique especially in increasing students’ speaking achievement. Keywords: Pow-Tega Technique, Speaking Achievement